2018
DOI: 10.1002/cam4.1375
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma‐activated pericytes support tumor growth via immunosuppression

Abstract: Glioblastoma multiforme is the most common and aggressive primary brain tumor, with an extremely poor prognosis. The lack of detailed knowledge about the cellular and molecular mechanisms involved in glioblastoma development restricts the design of efficient therapies. A recent study using state‐of‐art technologies explores the role of pericytes in the glioblastoma microenvironment. Glioblastoma‐activated pericytes develop an immunosuppressive phenotype, reducing T‐cell activation through the induction of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 98 publications
1
41
0
Order By: Relevance
“…In relation with that, the main angiogenic factor, vascular endothelial growth factor (VEGF), can inhibit the function of T cells and increase the recruitment of regulatory T cells (Tregs) and MDSCs 30 . Moreover, it has been shown that pericytes can support tumor growth via immunsuppression 31 . However, once in the tumors, the immune cells can also induce changes in the vascular compartment, as they have a strong pro-angiogenic role 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In relation with that, the main angiogenic factor, vascular endothelial growth factor (VEGF), can inhibit the function of T cells and increase the recruitment of regulatory T cells (Tregs) and MDSCs 30 . Moreover, it has been shown that pericytes can support tumor growth via immunsuppression 31 . However, once in the tumors, the immune cells can also induce changes in the vascular compartment, as they have a strong pro-angiogenic role 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…206,207 These active pericytes aid in immune suppression, remodeling of PVN, and protection of glioma stem cells (GSC) or glioma-initiating cells (GICs) from ischemic injuries. 208,209 Additionally, GSC recruits vascular pericytes via SDF1/CXCR4 signaling for angiogenesis. 210,211 GICs maintain self-renewal and differential properties by interacting with pericyte-derived endothelial cells via PDGF-NOS2-ID4 signaling.…”
Section: Role Of Neurovascular Unit In Ischemia and Glioma Astrocytesmentioning
confidence: 99%
“…In relation with that, the main angiogenic factor, vascular endothelial growth factor (VEGF), can inhibit the function of T cells and increase the recruitment of regulatory Tregs and MDSCs [31]. Moreover, it has been shown that pericytes can support tumor growth via immunosuppression [32]. However, once in the tumors, the immune cells can also induce changes in the vascular compartment as they have a strong pro-angiogenic role [33,34].…”
Section: Discussionmentioning
confidence: 99%